2013
DOI: 10.3906/biy-1210-27
|View full text |Cite
|
Sign up to set email alerts
|

Lignification response for rolled leaves of Ctenanthe setosa under long-term drought stress

Abstract: Leaf rolling is a dehydration avoidance mechanism for plants under drought stress. To understand how it affects the lignification process in response to long-term drought stress in Ctenanthe setosa plants that have the leaf-rolling mechanism, the enzymes in lignification were studied in unrolled leaves as a control and at 2 different leaf rolling indices at days 35 and 47 of the drought period. The results indicated that the activities of phenylalanine ammonia lyase, indole-3-acetic acid oxidase, soluble perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…It is known that cell wall peroxidases also influence growth and development of plant by limiting certain growth related reactions through collaboration with phenolic compounds, resulted in reduce wall extensibility. Enhanced PAL activity with subsequent effects on polyphenol oxidase, lignin content, ionic and cell wall-bound peroxidase activities is also supported by Terzi et al (2013). Our finding suggest that inoculation of maize with such isolates could provide salt tolerant ability of plants and serves as a useful tool for alleviating salinity stress.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is known that cell wall peroxidases also influence growth and development of plant by limiting certain growth related reactions through collaboration with phenolic compounds, resulted in reduce wall extensibility. Enhanced PAL activity with subsequent effects on polyphenol oxidase, lignin content, ionic and cell wall-bound peroxidase activities is also supported by Terzi et al (2013). Our finding suggest that inoculation of maize with such isolates could provide salt tolerant ability of plants and serves as a useful tool for alleviating salinity stress.…”
Section: Discussionsupporting
confidence: 72%
“…Pandey et al (2010) in a proteomic study, reported an enhanced PAL activity under drought stress in rice. Terzi et al (2013) also reported that, PAL activity increased up to 16-fold and also effects the polyphenol oxidase activities, ionically wall-bound peroxidase and lignin content in grey-maranta (Ctenanthe setosa) when exposed to drought stress. Resent review highlighted that PAL activity induced in response to different stresses, like salinity, drought, heavy metals, physical injuries and infection by virus, bacteria, fungi etc.…”
Section: Introductionmentioning
confidence: 80%
“…Results of Terzi et al (2013) suggested that an increase of water stress could induce lignification in rolled leaves of Ctenanthe setosa. In addition, rubbing the internodes of plants have reduced elongation with alteration of cell wall mechanical properties and accelerated lignification (De Jaegher et al, 1985).…”
Section: Lignin and Plant Hydraulicsmentioning
confidence: 99%
“…The accumulation of compatible solutes is a prerequisite for the adaptation of plants to osmotic stress imposed by drought stress (Serraj and Sinclair, 2002). Water content and water potential of plant tissue are considered as the physiologically appropriate integrators of drought effects; thus, relative water content (RWC) has been nominated as a suitable screening tool for drought-tolerant crops (Jones, 2007;Terzi et al, 2013). It has been reported that water loss can lower leaf water potentials, leading to reduced turgor, stomatal conductance, and photosynthesis, and finally to reduced seed yield.…”
Section: Introductionmentioning
confidence: 99%